(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
National games are an integral part of public education. Games were a requirement of folk pedagogy, which became an eternal habit when educating teenagers to love the people, land, homeland, morals, hard work, common sense, heroism and determination. Folk games and now remain the main factor in the process of initial preparation of young people for life. Raising a child is a parental duty of people, as well as a civic duty. That is why every parent tries to give his child a decent upbringing from birth. A lullaby is sung to hold the baby asleep. As soon as he gets up and walks gracefully, the tushoo kesuu ceremony is held. After that, the baby will begin to walk with confident steps and develop. And from now on, he will be taught games that will help him develop his mind, cultivate awareness, foresight in him, improve his health through various activities and form his outlook on life.